1982
DOI: 10.1073/pnas.79.15.4800
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of influenza A and B viruses: conservation of structural features in the hemagglutinin genes.

Abstract: The complete nucleotide sequence of the hemagglutinin (HA) gene of a type B influenza virus (B/Lee/40) was obtained by using cloned cDNA derived from the RNA segment. The gene is 1,882 nucleotides long and can code for a protein precursor of 584 amino acids. Structural features common to type A virus HAs are also conserved in the B virus HA. These include a hydrophobic signal peptide, hydrophobic NH2 and COOH termini of the HA2 subunit, and a HA1/HA2 cleavage site involving an arginine residue. The sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
125
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 32 publications
3
125
0
1
Order By: Relevance
“…The 60% level of homology between the nucleotide sequences of PB1 genes of A and B viruses is greater than the lowest homologies seen among nucleotide sequences of HAl subunits of the 14 HA subtypes of influenza A viruses (31.3 to 60.6%) (81). By comparison, the nucleotide sequences of the HAl subunits of influenza A and B viruses show 36% homology (92). The greater range in variation among influenza A virus HAl nucleotide sequences than between influenza B virus HAl and their influenza A virus counterparts suggests that influenza B viruses diverged from the A viruses after divergence of the early ancestors of present-day HA subtypes.…”
Section: Common Ancestry For Human and Classic Swinementioning
confidence: 79%
“…The 60% level of homology between the nucleotide sequences of PB1 genes of A and B viruses is greater than the lowest homologies seen among nucleotide sequences of HAl subunits of the 14 HA subtypes of influenza A viruses (31.3 to 60.6%) (81). By comparison, the nucleotide sequences of the HAl subunits of influenza A and B viruses show 36% homology (92). The greater range in variation among influenza A virus HAl nucleotide sequences than between influenza B virus HAl and their influenza A virus counterparts suggests that influenza B viruses diverged from the A viruses after divergence of the early ancestors of present-day HA subtypes.…”
Section: Common Ancestry For Human and Classic Swinementioning
confidence: 79%
“…In preliminary experiments and using standard techniques [7,8,18] we observed biochemical differences between the HA of A/Florence/2/84 in the two phases (J. Robertson and J. S. Oxford, unpublished). Of particular significance may be glycosylation site differences between the HAs.…”
Section: Resultsmentioning
confidence: 94%
“…3(d), in which there is a diagonal line that suggests homology between the N termini of NDV F~ and influenza C virus HA2. Homologies of the NDV F amino acid sequence to influenza A and B virus HA sequences (Porter et al, 1979;Krystal et al, 1982) were less strong (not shown).…”
Section: Resultsmentioning
confidence: 97%